2003
DOI: 10.1172/jci200316409
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of spontaneous autoimmune diabetes in NOD mice by quantification of autoreactive T cells in peripheral blood

Abstract: Type 1 diabetes is an autoimmune disorder characterized by the selective destruction of pancreatic β cells, resulting in insulin deficiency and hyperglycemia. Studies of both humans (1) and the NOD mouse model (2, 3) have shown that β cell destruction is mediated largely by T lymphocytes. Despite the direct β cell cytotoxic role of T cells during diabetes progression, prediction of disease in both humans and the NOD mouse has been based primarily on the presence of circulating autoantibodies to putative T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
185
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(209 citation statements)
references
References 32 publications
23
185
1
Order By: Relevance
“…The variability in detection of peripheral tetramer-binding cells, which was observed over several years in our study, may reflect true changes in cell frequency or, alternatively, changes in the sequestration and circulation of these cells over time. Similar variability has been previously reported in a mouse model of diabetes, using class I tetramer detection strategies [20]. Recently, a study of tetramer-positive cells in celiac disease demonstrated successful detection in peripheral blood samples after antigen challenge in vivo, suggesting the possibility that autoreactive cells may persist in extravascular sites, presumably in the target organ or associated lymphatics, and that they can be mobilized for detection via sampling of the peripheral blood [18].…”
Section: Discussionsupporting
confidence: 75%
“…The variability in detection of peripheral tetramer-binding cells, which was observed over several years in our study, may reflect true changes in cell frequency or, alternatively, changes in the sequestration and circulation of these cells over time. Similar variability has been previously reported in a mouse model of diabetes, using class I tetramer detection strategies [20]. Recently, a study of tetramer-positive cells in celiac disease demonstrated successful detection in peripheral blood samples after antigen challenge in vivo, suggesting the possibility that autoreactive cells may persist in extravascular sites, presumably in the target organ or associated lymphatics, and that they can be mobilized for detection via sampling of the peripheral blood [18].…”
Section: Discussionsupporting
confidence: 75%
“…For some of these novel autoantigens, there is data suggesting their significant role in the development of T1D, such as the existence of T-cell clones capable of transferring the disease or immunotherapy using antigenic peptides derived from these autoantigens (Table 1). These include islet-specific glusose-6-phosphatase catalytic subunitrelated protein (IGRP), ZnT8 and, interestingly, the neurotropic factor S100beta and the glial fibrillary acidic protein (GFAP) (Gomez-Tourino et al 2010Lieberman et al 2003;Trudeau et al 2003;Winer et al 2003), the latter two being antigens not expressed by the beta cells themselves but by a group of nerve cells surrounding the islets called the peri-islet Schwann cells (pSC) which makes their role in T1D pathogenesis controversial.…”
Section: T Lymphocytes In T1d: Targets and Peripheral Detectionmentioning
confidence: 99%
“…Its relevance to T1D derives from the fact that in the NOD mice the number of IGRP-specific CD8 + T cells correlate with the future development of clinical disease (Trudeau et al 2003).…”
Section: T Lymphocytes In T1d: Targets and Peripheral Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…These CTL recognise peptide sequences from the insulin B chain [15][16][17][18][19][20][21][22][23] (G9C8 clone) [2], islet-specific glucose-6-phosphatase catalytic subunit-related protein (IGRP 206-214 ; 8.3 clone) [3] and dystrophia myotonica kinase (AI4 clone) [4]. Together, these CTL populations constitute a large proportion (up to 60%) of the CD8 + T cells within the pancreatic islets of prediabetic NOD mice [4,5].…”
Section: Introductionmentioning
confidence: 99%